The use of tabletop exercises in nuclear security education. (2nd July 2018) - Shattan, Michael; Seybert, Adam; Gilbreath, Robert Boone; Dahunsi, Stephen; Hall, Howard L.
Abstract : Purpose: The purpose of this paper is to explore the role of tabletop exercises (TTXs) in graduate nuclear security education, their effectiveness and their relationship to traditional forms of classroom instruction. The paper highlights both the benefits and challenges of TTX implementation—the former including higher student motivation and material retention, and the latter including motivational shifts toward "winning" and possible student exclusionary behavior. Design/methodology/approach: Survey results from 49 former students in a US university were collected electronically and combined with anecdotal evidence from student, facilitator and teaching assistant interviews following five iterations of a specifically designed, semester-long, TTX case study. The case study focused on securing a fictional nuclear facility. Findings: Students found the TTX more memorable and retained more course material when asked to compare the TTX's effectiveness to long-term course projects in other courses. Their in-class motivations tended to shift from traditional classroom motivations toward "winning, " and "not letting down their classmates." In some iterations, students also observed classmates becoming more tempted to cheat or otherwise violate academic ethics. Mitigation strategies to prevent such temptations (e.g. removing direct student vs student TTX structures) were found to be effective. Originality/value: This is the first report on the effective use of a semester-long TTX in a graduate nuclear security classroom. The flexibility of this instructional tool demonstrates its applicability to other classroom subjects including homeland security, emergency management, disease outbreak management and public policy among others.